2008
DOI: 10.1007/s11145-008-9141-y
|View full text |Cite
|
Sign up to set email alerts
|

Academic vocabulary and middle school English learners: an intervention study

Abstract: The goal of this experimental intervention study was to determine if evidence-based instructional strategies for general vocabulary words are effective with middle school English learner (EL) students and academic vocabulary words. Participants showed significantly more growth in their knowledge of academic vocabulary during the treatment condition than during the control condition. A secondary goal of this study was to examine the predictive utility of students' English language proficiency, and students' gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 45 publications
0
63
0
Order By: Relevance
“…We should note that language relatedness generally bestows other types of facilitation to L2 groups, for example, in terms of morpho-syntax, word, sentence-level and pronunciation. Our findings add to the intervention research using the Academic Word List (Lesaux, Kieffer, Faller, & Kelley, 2010;Snow, Lawrence, & White, 2009;Townsend & Collins, 2009) and suggest that EAP instructors need to be aware of their students' L1 and their needs regarding academic vocabulary. Some students may be familiar with Latin-Greek words while some others may need additional support.…”
Section: Resultsmentioning
confidence: 57%
“…We should note that language relatedness generally bestows other types of facilitation to L2 groups, for example, in terms of morpho-syntax, word, sentence-level and pronunciation. Our findings add to the intervention research using the Academic Word List (Lesaux, Kieffer, Faller, & Kelley, 2010;Snow, Lawrence, & White, 2009;Townsend & Collins, 2009) and suggest that EAP instructors need to be aware of their students' L1 and their needs regarding academic vocabulary. Some students may be familiar with Latin-Greek words while some others may need additional support.…”
Section: Resultsmentioning
confidence: 57%
“…In their study on the effectiveness of an after-school program for Spanish-speaking middle school LEP students, Townsend and Collins (2009) showed that a well-designed research-based intervention can be beneficial for enhancing academic vocabulary knowledge of language minority students. In other studies (August et al, 2009;Lesaux et al, 2010;Proctor et al, 2011), researchers found that the effects of their treatment did not differ according to the language minority status of the students.…”
Section: Importance Of Academic Vocabulary Knowledgementioning
confidence: 99%
“…Drama lessons provide a means of building oral language skills that is useful for all students. A growing body of literature has pointed out that best practices for promoting vocabulary knowledge among ELLs have also proven to be best practices for building breadth and depth of vocabulary knowledge among native English speakers (August et al 2005;Beck and McKeown 2007;Biemiller and Boote 2006;Blanchowicz and Fisher 2004;Carlo et al 2004;Townsend and Collins 2009).…”
Section: Theater Arts and Language Developmentmentioning
confidence: 99%